Development of Scratch 3.0-Based Science Educational Game on Solar System Material to Improve Learning Outcomes of 6th Grade Elementary School Students - Wachdani, Rizky Ayu; Thohir, M. Anas; Utama, Candra (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2025)
This research and development aims to create a Scratch 3.0- based science education game product on solar system material that is valid, practical, and effective to improving students’ learning outcomes. The method used is Research and Development (RD) with the ADDIE development model. The subjects in this research and development consisted of material expert and media experts also 30 students and a 6th grade teacher of SDN Keniten 1. The data collection instrument consisted of a questionnaire, pre test, and post test. The validity test results based on material experts obtained an average percentage of 91.1%, while based on media experts obtained an average percentage of 95.3%, both of that were included in the very valid category. The practicality test from students obtained a score of 98.9% and from the teacher obtained a score of 95.4%, both of that were included in the very practical category. The results of the data prerequisite test were normally distributed and the results of the paired sample t-test effectiveness test obtained a Sig. (2-tailed) of 0.000 0.05, it can be summed up that ????0 is rejected and ???????? is accepted or there is a significant difference between the pre and post test results. Thus, the use of Scratch 3.0-based science educational games is declared very valid, practical, and significantly effective to improve students’ learning outcomes on solar system material.